Preparation and Performance of Regenerated Al2O3-Coated Cathode Material LiNi0.8Co0.15Al0.05O2 from Spent Power Lithium-Ion Batteries - Liwen Ma; Guangyun Liu; Yuehua Wang; Xiaoli Xi (Molecules, 2023)
In this study, LiNi0.8Co0.15Al0.05O2@x%Al2O3-coated cathode materials were regeneratively compounded by the solid-phase sintering method, and their structural characterization and electrochemical performance were systematically analyzed. The regenerated ternary cathode material precursor synthesized by the co-precipitation method was roasted with lithium carbonate at a molar ratio of 1:1.1, and then completely mixed with different contents of aluminum hydroxide. The combined materials were then sintered at 800 °C for 15 h to obtain the regenerated coated cathode material, LiNi0.8Co0.15Al0.05O2@x%Al2O3. The thermogravimetry analysis, phase composition, morphological characteristics, and other tests show that when the added content of aluminum hydroxide is 3%, the regenerated cathode material, LiNi0.8Co0.15Al0.05O2@1.5%Al2O3, exhibits the highest-order layered structure with Al2O3 coating. This material can better inhibit the production of Ni2+, and improve material structure and electrochemical properties. The first charge–discharge efficiency of the battery assembled with this regenerated cathode material is 97.4%, a 50-cycle capacity retention is 93.4%, and a 100-cycle capacity retention is 87.6%. The first charge–discharge efficiency is far better than that of the uncoated regenerated battery.